Teaching Ethics amidst Transitions (International Transitions, 2024)
This article examines the ethical challenges in a rapidly changing technological world, emphasizing the importance of ethics in education in light of the swift evolution of technologies, society, and the environment. It acknowledges the necessity of teaching ethics to prepare future leaders capable of critical thinking in a context of abundant moral dilemmas and shifting ethical standards. Pedagogical strategies for teaching ethics include active methods such as case studies, debates, and role-playing, promoting ethical decision-making and a deeper understanding of moral issues. Creating a learning environment that encourages exploration and debate is essential for training ethical leaders ready to make positive contributions in a complex world.